Answer:
y = 3
x = 2
Step-by-step explanation:
-5x + 4y = 2
9x - 4y = 6
Sum both eq.
-5x + 9x = 4x
+4y - 4y = 0
2 + 6 = 8
then:
4x + 0 = 8
4x = 8
x = 8/4
x = 2
from the first eq.
-5x + 4y = 2
-5*2 + 4y = 2
-10 + 4y = 2
4y = 2 + 10
4y = 12
y = 12/4
y = 3
Check:
from the second eq.
9x - 4y = 6
9*2 - 4*3 = 6
18 - 12 = 6
Answer:
A change in a species that helps it survive
Step-by-step explanation:
i took life science in 7th grade, and another word for this is a mutation (kinda... pls dont make me go there...)
Sally had about a half cup of pudding. If you make both numbers have the same denominator, you would get 8/36 and 9/36. Add them together, and you get 17/36, which is almost half.
First of all, you spell $dollars with an a not an e. Second of all, the answer is $4.40
Answer:
The answer is 2
Step-by-step explanation:
4=2s
Divide both sides by 2
4/2=2
s=2